Establishment of an in vitro hairless guinea pig dermal model - Samantha Emma Sarles; Priscilla Lee; Linnzi Wright; Daniel Angelini (PLoS ONE, 2026)
Hairless guinea pigs (HGP) make a desirable model for percutaneous exposure because they do not need to be clipped and are lower in cost and less sentient than swine. Current data leaves gaps in data translation and scaling from animal to human and from cells to whole organisms. The establishment and tracking of in vitro cell cultures from animals from an in-house colony allows for highly controllable and reportable data for data translation. We report the isolation, culture, methods optimization, characterization, and toxicant exposure of HGP dermal fibroblasts (HGP-DF) from the in-house HGP breeding colony at U.S. Army Combat Capabilities Development Command Chemical Biological Center (DEVCOM CBC). We successfully isolated HGP-DF from the forelimb and hindlimb skin of several HGP. Fibroblasts exited tissue within 14 days. All trypsin and media types tested for cell maintenance yielded cells with greater than 95% viability during passaging. Cells were stored under cryopreservation and exhibited acceptable viability for several passages after thawing. Fluorescently stained HGP-DF exhibited similar morphology as vendor certified human dermal fibroblasts. HGP-DF were more sensitive than human dermal fibroblasts to a toxic exposure, with median lethal concentrations of 1 mM and 0.3 mM for human cells and hairless guinea pig cells, respectively. This follows a similar trend as observed in whole organism data from the same toxicant. This work marks the first documented protocol on isolation, culture, characterization, and exposure of HGP cells. HGP-DF enable an intermediate model between human cells and in vivo models that may enable validation of in vitro models against animal models. Future work should address limitations of the present study, including evaluating phenotypic changes of cells following cryopreservation and immunohistochemistry compared to vendor certified controls to confirm dermal fibroblast phenotype.